Master of Information Science (MIS) - Kabale University (Kabale University, 2022)
Information Science is a wide field which covers many academic fields like Library science, Records management, Documentation, Archives, Informatics, Informetrics and Bibliometrics. The proposed course content will enrich students to understand the core ideas in Library, Records, Documentation, Archives and Information management generally which helps to position graduates in global practice across academic disciplines. The program will be run on regular basis (week end) and shall be a two-year academic program. This program is by course work and dissertation. The structure and scope of this program will engage students in rigorous course work and research that spans over the duration of the program. The main objective of the program is to raise the profile of the profession by producing highly trained professionals who are competent and proficient in matters pertaining to information management.